Immunogenicity and safety of a novel monovalent high-dose inactivated poliovirus type 2 vaccine in infants: a comparative, observer-blind, randomised, controlled trial. Issue 3 (March 2016) - Sáez-Llorens, Xavier; Clemens, Ralf; Leroux-Roels, Geert; Jimeno, José; Clemens, Sue Ann Costa; Weldon, William C; Oberste, M Steven; Molina, Natanael; Bandyopadhyay, Ananda S
Summary: Background: Following the proposed worldwide switch from trivalent oral poliovirus vaccine (tOPV) to bivalent types 1 and 3 OPV (bOPV) in 2016, inactivated poliovirus vaccine (IPV) will be the only source of protection against poliovirus type 2. With most countries opting for one dose of IPV in routine immunisation schedules during this transition because of cost and manufacturing constraints, optimisation of protection against all poliovirus types will be a priority of the global eradication programme. We assessed the immunogenicity and safety of a novel monovalent high-dose inactivated poliovirus type 2 vaccine (mIPV2HD) in infants. Methods: This observer-blind, comparative, randomised controlled trial was done in a single centre in Panama. We enrolled healthy infants who had not received any previous vaccination against poliovirus. Infants were randomly assigned (1:1) by computer-generated randomisation sequence to receive a single dose of either mIPV2HD or standard trivalent IPV given concurrently with a third dose of bOPV at 14 weeks of age. At 18 weeks, all infants were challenged with one dose of monovalent type 2 OPV (mOPV2). Primary endpoints were seroconversion and median antibody titres to type 2 poliovirus 4 weeks after vaccination with mIPV2HD or IPV; and safety (as determined by the proportion and nature of serious adverse events and important medical events for 8 weeks after vaccination). The primary immunogenicity analyses included all participants for whom a post-vaccination blood sample was available. All randomised participants were included in the safety analyses. This trial is registered withClinicalTrials.gov, numberNCT02111135 . Findings: Between April 14 and May 9, 2014, 233 children were enrolled and randomly assigned to receive mIPV2HD (117 infants) or IPV (116 infants). 4 weeks after vaccination with mIPV2HD or IPV, seroconversion to poliovirus type 2 was recorded in 107 (93·0%, 95% CI 86·8–96·9) of 115 infants in the mIPV2HD group compared with 86 (74·8%, 65·8–82·4) of 115 infants in the IPV group (difference between groups 18·3%, 95% CI 5·0–31·1; p<0·0001), and median antibody titres against poliovirus type 2 were 181 (95% CI 72·0–362·0) in the mIPV2HD group and 36 (18·0–113·8) in the IPV group (difference between groups 98·8, 95% CI 60·7–136·9; p<0·0001). Serious adverse events were reported for six (5%) of 117 infants in the mIPV2HD group and seven (6%) of 116 infants in the IPV group during the 8-week period after vaccination; none were related to vaccination. No important medical events were reported. Interpretation: Our findings lend support to the use of mIPV2HD as an option for stockpiling for outbreak response or primary protection in selected areas at risk for emergence of poliovirus type 2 during the next phase of the polio eradication plan. Funding: Bill & Melinda Gates Foundation.